Manajemen Organisasi Pembelajar di Institusi Publik - Pangihutan Marlin Marpaung (Jurnal Widyaiswara Indonesia, 2020)
Manajemen Organisasi Pembelajar adalah program pengembangan kompetensi ASN terpadu dan berkelanjutan dalam rangka meningkatkan kualitas pelayanan publik ASN yang dinilai masih jauh dari tuntutan globalisasi. Penelitian ini bertujuan menganalisis kebiasaan dan perilaku belajar ASN; mengidentifikasi pola kepemimpinan mengelola strategi pembelajaran; mengidentifikasi peran sarana dan prasarana (sarpras) pembelajaran; dan menguraikan langkah strategis pembina kepegawaian mengelola pembelajaran. Metode penelitian kualitatif menggunakan kuesioner Organizational Learning Self-Assessment kepada 112 pimpinan ASN yang telah mengikuti organisasi pembelajar dalam Pelatihan Kepemimpinan. Penelitian juga menghimpun praktik organisasi pembelajar di 10 Kementerian, LPNK, Propinsi, Kabupaten dan Kota yang berhasil mengembangkan kompetensi ASN melalui program non-pelatihan. Hasil penelitian menunjukkan bahwa dari skala 1 – 5, nilai rata-rata 4.25 (sangat baik) untuk semua butir tujuan penelitian. Analisis kebiasaan dan perilaku belajar ASN nilai 4.46; Potret kepemimpinan dan arah strategi pembelajaran sebesar 4.30; dan identifikasi peran sarpras pembelajaran sebesar 4.01. Peta kekuatan pada aspek komunikasi pembelajaran; ketersediaan umpanbalik; relevansi tujuan pembelajaran; pimpinan sebagai model pembelajar; dan teknologi sarpras mendukung pembelajaran. Aspek pembenahan diperlukan pengelolaan permasalahan pembelajaran; peran pimpinan kurang memberi reward pembelajaran; menetapkan tujuan pembelajaran saat merencanakan kegiatan; dan penyediaan tenaga ahli mengelola coaching pembelajaran. Diperlukan langkah strategis pembina kepegawaian dan pimpinan unit lini dengan menerbitkan kebijakan pengelolaan pembelajaran dari tahap merancang sampai mengevaluasi pembelajaran. Peran lembaga pelatihan tidak hanya menyelenggarakan pelatihan mandatory; tetapi juga mengembangkan kompetensi pimpinan unit lini mengelola pembelajaran. Learning Organization management is integrated and continuous for Civil Service Apparatus (ASN, in short) competency development programs, in order to increase public service quality by ASN that is still considered not in line with globalization demands. The research objectives are to analyze organizational habits and learning behavior; to identify leadership’s role in learning direction; to identify impact of organizational sources to learning; and to elaborate strategic steps of personnel in managing learning organization. Qualitative research method utilizes published questionnaire on Organizational Learning Self-Assessment given to 112 leaders of ASN that had attended learning organization session in Leadership Training. The research also collects learning organization practices from 10 selected ministries, non-ministries, and local government that had been successful to develop competency of ASN through learning organization programs. The findings show that, out of 1 to 5 scale, the average score of 4,25 (very good results). The score on organizational habits and learning behavior is 4.46; leadership’s role in learning direction is 4.30; and identification impact of organizational sources to learning is 4,01. The strengths are on sharing communication to boost learning; the leaders as models of learning that provide feedback; and availability of resources and technology to support learning. Limitations are on the lack of competency in managing learning challenges; learning objectives were not considered when planning unit activities; and the absence of coaching in learning.To achieve success in learning organization, regulations on learning is needed to facilitate learning feedback.To achieve success in learning organization, regulations on learning is needed to facilitate learning feedback. Collaboration of work units responsible to personnel with unit leaders is crucial from planning until evaluation of learning. And th role of training units should not implement mandatory trainings only; but also to develop competency unit leaders in managing learning organization in their respective work units.